2023
DOI: 10.1007/s11547-023-01652-3
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of care for re-irradiation in locally recurrent rectal cancer: a national survey on behalf of the AIRO gastrointestinal tumors study group

Abstract: Purpose Radical resection (R0) represents the best curative treatment for local recurrence (LR) rectal cancer. Re-irradiation (re-RT) can increase the rate of R0 resection. Currently, there is a lack of guidelines on Re-RT for LR rectal cancer. The Italian Association of Radiation and clinical oncology for gastrointestinal tumors (AIRO-GI) study group released a national survey to investigate the current clinical practice of external beam radiation therapy in these patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Therefore, reirradiation could be a treatment option if complete surgical resection is not feasible or the patient denies salvage surgery for LRRC. The results of an Italian national survey showed that reirradiation was an option for neoadjuvant treatment in resectable and unresectable LRRC in 55 and 75% of cases, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reirradiation could be a treatment option if complete surgical resection is not feasible or the patient denies salvage surgery for LRRC. The results of an Italian national survey showed that reirradiation was an option for neoadjuvant treatment in resectable and unresectable LRRC in 55 and 75% of cases, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an Italian national survey, the irradiation of the cumulative dose of EQD2 (equivalent dose in 2 Gy) was 90–100 Gy considering the previous RT dose [ 19 ]. In the present study, the dose with the median cumulative EQD2 (α/β = 10) was high, at 121 Gy ( Table 2 ); unfortunately, four patients (40%) had further local recurrence in the reirradiation field.…”
Section: Discussionmentioning
confidence: 99%
“…These reviews were mainly based on studies in which 3D techniques were used [17,18]. Regarding CIRT, the systematic review by Venkatesulu et al reports interesting results and describes CIRT as a promising new technology when re-irradiation is required [27] A recent Italian study published by the Italian Association of Radiation and Clinical Oncology for Gastrointestinal Tumors (AIRO-GI) showed that most Italian centers have advanced technologies such as VMAT/IMRT/SBRT and daily image monitoring, which have led to breakthroughs in dose and fractionation [13].…”
Section: Discussionmentioning
confidence: 99%
“…The trouble concerning re-RT in this group of patients is related both in terms of the received dose of the organs at risk (OARs) and the time elapsed between the two irradiations. There are not enough studies on dose constraints for OARs, so radiation oncologists do not have clear guidelines on the doses that can be administered to avoid acute and late side effects [13]. Administering a suboptimal dose for fear of side effects can result in failure to control the disease or leave patients permanently inoperable [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation